Pengelolaan Media Sosial Gereja Katolik Paroki Keluarga Kudus Pasar Minggu dalam Penyebaran Informasi Kegiatan Keagamaan - Ave Airiza Gunanto (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to determine how social media management is carried out by the Public Relations division of Gereja Katolik Paroki Keluarga Kudus Pasar Minggu in disseminating information regarding religious activities as a form of online public relations. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The results show that social media management at Gereja Katolik Paroki Keluarga Kudus Pasar Minggu is implemented through the four-step public relations model by Cutlip, Center, and Broom, namely defining public relations problems, planning and programming, taking action and communicating, and evaluating the program. In the defining public relations problems stage, social media administrators analyze the congregation’s information needs and select appropriate media platforms. In the planning and programming stage, content planning, communication objectives, and task distribution are arranged. The taking action and communicating stage is carried out through the publication of church activities, mass schedules, spiritual services, and interaction with the congregation via social media. The evaluating the program stage is conducted through engagement monitoring, evaluation of congregation responses, and internal evaluation meetings.